Combination of extractive techniques followed by HPLC-MS/MS analysis to monitor ent-agathic acid in fish treated with Copaifera duckei Dwyer - da Silva, Jonas Joaquim Mangabeira; Campanharo, Sarah Chagas; da Silva, Agnaldo Fernando Baldo; de Jesus, Raphael Barbetta [UNESP]; Figueredo, Tais Alexandra Mário; Pilarski, Fabiana [UNESP]; Heleno, Vladimir Constantino Gomes; Paschoal, Jonas Augusto Rizzato (Elsevier, 2023)
Plants are used as therapeutic alternatives in Veterinary Medicine, including therapies for food-producing animals. However, these medicinal resources can sometimes contain dangerous substances, and when used in animals that supply food, they stand out from the point of view of food safety. The diterpene ent-agathic acid, a component of Copaifera duckei oleoresin, is an example of substances already described with toxic activity in mammals. Thus, this study aimed to propose combining two extractive techniques followed by high-performance liquid chromatography coupled mass spectrometry analysis to monitor residues of ent-agathic acid in Piaractus mesopotamicus fillet treated in an immersion bath with Copaifera duckei oleoresin. An optimized combination of solid–liquid extraction (using acidified acetonitrile) and dispersive liquid–liquid microextraction (using acidified water and chloroform as dispersive and extracting solvent, respectively) was performed to recover the target analyte, added to the development of HPLC-MS/MS method with adequate validation parameters to quantify the ent-agathic acid present in the fish fillet. In vivo tests of residual persistence of ent-agathic acid in fishes treated with C. duckei oleoresin were performed, indicating the non-detection of the target diterpene (< 6.1 µg/mL). The combined extractive procedure followed by quantitative analysis in the in vivo test of residual persistence of the target analyte in fish indicated the absence of ent-agathic acid in all samples. Thus, the data found might contribute to understanding the use of oleoresins from C. duckei as an alternative to traditional veterinary products.
Keywords: Aquaculture; DLLME; Extraction; Food safety; LC-MS/MS; Toxic residue